Comparative Study of Learning Outcomes Between the Application of the Seminar Method and the Preparatory Assignment Method in History Learning - Anwar, Khoirul (Indonesian Journal of History Education, 2016)
This is a comparative study of two methods of learning: the experimental method and the method of assignment preparation seminar. The purpose of this study was to determine the learning outcomes of students who were taught by both methods, as well as to know the difference between the methods of implementation of tasks and methods of preparation seminar. The approach of this research is to experimentally study the entire population of students in class XI IPS SMA 3 Demak, while the sample taken is class 1 and class XI IPS 3. Study results indicate that a class of students who were taught using seminars obtained better results than the class taught by the method of preparation tasks, although both performed equally well. This study suggests that Learners need to be encouraged to be active participants in learning; seminar methods and preparation task methods can be applied in teaching history to make students active in education.